Facile Synthesis of CuO Nanosheets and Efficient Degradation of Rhodamine B in a Copper Oxide/Ascorbic Acid/Hydrogen Peroxide System: Kinetics, Fate of Ascorbic Acid, and Mechanism. Issue 20 (27th May 2020) - Xiao, Bing; Wu, Meng; Wang, Yun; Chen, Rufen; Liu, Hui
Abstract: CuO nanosheet was successfully prepared via a simple, green hydrothermal method. The resulted product was characterized by various technologies. CuO combined with trace ascorbic acid exhibited excellent Fenton‐like catalytic activity for Rhodamine B degradation. 80 % of RhB degradation occurred in the first 10 min and ascorbic acid was transformed to dehydroascorbic acid at this stage. When the RhB degradation reaction ended, the mineralization of ascorbic acid commenced and finally the ascorbic acid was mineralized to CO2 and H2 O. The role of ascorbic acid was to accelerate the two cycles (≡Cu II →≡Cu III →≡Cu II and ≡Cu I →≡Cu II →≡Cu I ) on the surface of CuO particles, which results in the continuous generation of abundant free radicals and rapid degradation of pollutants. The rapid degradation kinetics can be described by Behnajady‐Modirshahla‐Ghanbery equation. The rate constant of HO generation was 3.7 × 10 −2 s −1 and the most utilization efficiency of H2 O2 reached 75 %. The CuO/ascorbic acid catalyst has environmentally friendly features, thereby highlighting its practical utility for wastewater treatment. Abstract : An effective heterogeneous Fenton‐like catalyst by combining the traditional CuO with an environmentally benign reductant ascorbic acid to activate H2 O2 and degrade RhB. The role of ascorbic acid was to accelerate the two cycles (≡Cu II →≡Cu III →≡Cu II and ≡Cu I →≡Cu II →≡Cu I ) on the surface of CuO particles, which results in the continuous generation of abundant free radicals and rapid degradation of pollutants.